The book of women's friendship - Cooke, Rachel (Journalist) (W.W. Norton & Company, 2025)
"The first major anthology devoted to women's friendship drawn from fiction, diaries, poetry, and letters. As Marilynne Robinson writes in her 1980 novel, Housekeeping, "Having a sister or friend is like sitting at night in a lighted house." Bringing together work by more than 100 writers, The Book of Women's Friendship explores the rich subject of friendship between women from every angle: its particular intensity and miraculous ease, its tendency to wax and wane, its role not only as a comfort and a privilege, but as vital to our health. Friendship has never been more highly debated, and loneliness more prevalent. Yet women's friendships have repeatedly been neglected or minimized in storytelling, fallen by the wayside of male relationships. In the first major anthology dedicated to women's friendship--and the first serious anthology about friendship published in more than three decades--editor Rachel Cooke looks to art to find the words to capture women's platonic love. Compiling selections from novels, poems, diaries, letters, comics, and graphic novels about women's friendship, she places work from a diverse array of artists in conversation across time and place. With excerpts from Jane Austen to Edith Wharton and Virginia Woolf, from Dolly Alderton to Sarah Waters, and from Zadie Smith to Meg Wolitzer, The Book of Women's Friendship celebrates and investigates friendship between women, from first encounters to final farewells, from falling out to making up again. This book takes the shape of a human life, beginning with early efforts at friend-making and -breaking in childhood to chance collisions in adulthood. It contemplates (though not for too long) the flip side of friendship, which is not enmity, but loneliness; celebrates solidarity in all its guises; and ends with loss, the moment of goodbye. Warm, clever, and full of some of the most beautiful writing on friendship ever published, The Book of Women's Friendship is also an act of friendship itself, dedicated to Cooke's best friend, in the end becoming a book full of all the lovely, impossible, unsayable things that one friend might be moved to give to another."--Publishe